Mineral profile of abandoned cows suffering from anestrus - SHARMA, ROHIT; SINGH, MADHUMEET; KUMAR, PRAVESH; SHARMA, AKSHAY (The Indian Journal of Animal Sciences, 2020)
The present investigation was carried out with an objective of studying the mineral profile in abandoned cows affected by anestrus (N=83). Overall 83 abandoned cows kept in 18 Goshalas were diagnosed to be affected with anestrus. The macro minerals, i.e. calcium (Ca), magnesium (Mg) and microminerals, viz. copper (Cu), zinc (Zn), cobalt (Co) and manganese (Mn) were estimated from plasma. Nutritional supplementation led to a successful recovery in 42.17% cows. Mineral profile suggested that inorganic phosphorus and copper concentration increased significantly in recovered anestrus cows. All other minerals also witnessed a non-significant increase in recovered as well as nonrecovered cows after treatment. In conclusion, anestrus could be successfully treated to an extent following nutritional supplementation.